(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The rate of unemployment growth in the province of Riau Islands is very high. The unemployment rate, particularly for SMK, is 12.98%; about 8,959; for SMA, 10.91% or about 7,530 people. The issues are poor work ethics, insufficient problem-solving strategies, critical thinking skills, the ability to work and the consistency of business performance, just skills which are deemed good enough. This thesis seeks to ana-lyze the efficacy of a Vocational High School Air Conditioner Job Simulator Learning Model. The study design was quasi-experimental, applied to learning in the experimental and control lessons. The study included students taking the Air Conditioner course. The method used was the Efficiency Test. The find-ings showed that the student performance test results with the Employability skill learning model based on the trainer simulator air conditioner were higher than the results of the work-oriented training performance test. Thus it can be inferred that the use of the Air Conditioner Simulator Employability Skill Learning Model is more efficient than learning on a work basis.